2021
DOI: 10.1055/s-0041-1725078
|View full text |Cite
|
Sign up to set email alerts
|

Croup: A Rare Manifestation of Coronavirus Disease 2019

Abstract: Croup is an acute inflammatory condition affecting upper airways and commonly seen in children with younger age group. Croup is most commonly due to acute viral infection and rarely because of bacterial and atypical agents. Here, we report a 3-month-old child who presented to us with classic signs and symptoms of croup and was also positive for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Child's mother also tested positive for SARS-CoV-2. SARS-CoV-2 infection presenting with stridor and croup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“… 10 Before the omicron variant surge, few cases of croup caused by COVID-19 were reported in children. 11 12 13 14 15 16 Previously reported cases indicate that COVID-19-associated croup can be treated in the same manner as other viral causes of croup. 11 13 15 16 In two cases, endotracheal intubation was performed due to secondary bacterial tracheitis and multisystem inflammatory syndrome in children.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 10 Before the omicron variant surge, few cases of croup caused by COVID-19 were reported in children. 11 12 13 14 15 16 Previously reported cases indicate that COVID-19-associated croup can be treated in the same manner as other viral causes of croup. 11 13 15 16 In two cases, endotracheal intubation was performed due to secondary bacterial tracheitis and multisystem inflammatory syndrome in children.…”
Section: Discussionmentioning
confidence: 99%
“… 11 12 13 14 15 16 Previously reported cases indicate that COVID-19-associated croup can be treated in the same manner as other viral causes of croup. 11 13 15 16 In two cases, endotracheal intubation was performed due to secondary bacterial tracheitis and multisystem inflammatory syndrome in children. 12 14 Three retrospective analyses of COVID-19-associated croup have demonstrated that the incidence of croup significantly increased during periods where the omicron variant was circulating.…”
Section: Discussionmentioning
confidence: 99%